1988
DOI: 10.1007/bf01969103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on the effects of erythromycin A and azithromycin upon extracellular release of lysosomal enzymes in inflammatory processes

Abstract: In the present studies the in vivo and in vitro effects of erythromycin A and azithromycin, a new type of macrolide (Fig. 2.), were investigated upon extracellular release of lysosomal enzymes, beta-glucuronidase (beta-Gluc) and beta-N-acetylglucosaminidase (beta-Glm) by using two experimental model systems: in vivo-adjuvant-induced arthritis in rats and in vitro- human polymorphonuclear leucocytes (PMNL) exposed to bovine serum albumin/anti-bovine serum albumin (BSA/anti-BSA), immune complex. Administrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 23 publications
(21 reference statements)
1
14
0
1
Order By: Relevance
“…Preliminary data from our laboratory indicate that similar properties are observed with clarithromycin and roxithromycin (21), two 14-membered ring macrolides which are also heavily concentrated by phagocytes (17), possibly inside azurophilic granules (8). Azithromycin, an azalide reported to display tremendous intraphagocytic accumulation by protonation trapping in lysosomes (32), has been shown to decrease the extracellular release of neutrophil intragranular enzymes (7 (6,11). In the case of common pathogens which trigger phagocytosis and do not inhibit phagolysosomal fusion, the intragranular location of these drugs may concur with their bioactivity (against Staphylococcus aureus, Streptococcus pneumoniae, etc.)…”
Section: Methodsmentioning
confidence: 65%
“…Preliminary data from our laboratory indicate that similar properties are observed with clarithromycin and roxithromycin (21), two 14-membered ring macrolides which are also heavily concentrated by phagocytes (17), possibly inside azurophilic granules (8). Azithromycin, an azalide reported to display tremendous intraphagocytic accumulation by protonation trapping in lysosomes (32), has been shown to decrease the extracellular release of neutrophil intragranular enzymes (7 (6,11). In the case of common pathogens which trigger phagocytosis and do not inhibit phagolysosomal fusion, the intragranular location of these drugs may concur with their bioactivity (against Staphylococcus aureus, Streptococcus pneumoniae, etc.)…”
Section: Methodsmentioning
confidence: 65%
“…The drug may modify the lysosomal membrane in such a way that it is capable of fusing with the plasma membrane and thereby preventing the discharge of acid hydrolases or by inhibiting the release of lysosomal enzymes. 51) Numerous reports have appeared on the inhibition of acid hydrolases by flavonoids. 52) Studies of cancer treatment in experimental animals have assessed the impact of a wide variety of flavonoids and a selected few isoflavones for their efficacy in inhibiting cancer in a number of animal models.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been verified in phagocytic and nonphagocytic human and animal cells (6,9,45,50,51). The possibility that the intragranular location alters the correct functioning of this cellular compartment (exocytosis, phagolysosomal fusion) has been little explored (1,8,30). Recently, we have demonstrated that various 14-memberedring macrolides induce PMN degranulation (1,30) and that extracellular calcium is required for this phenomenon (31).…”
Section: ؉mentioning
confidence: 99%